BlueYou: uma plataforma de comunicação ciente de contexto baseada em serviços para computação móvel - Almeida, Ricardo Aparecido Perez de (Universidade Federal de São Carlos, 2011)
The raising number of mobile devices with high computing capacity and support to different wireless transmission technologies has been motivating the creation of communication services capable to provide information to users anytime and anywhere. Particularly, it s possible to note the existence of a massive number of devices equipped with the Bluetooth communication technology, available in millions of devices. Plenty of mechanisms for content dissemination and sharing have been developed for use with Bluetooth technology in different application scenarios, such as mobile marketing, u-commerce and mobile learning. Most of these mechanisms, however, are used for specific purposes or are highly dependent on a communication infrastructure. Moreover, most of them use only little information about different contexts related to the environment, the users and the state of the devices involved in the transmissions. This work presents the project and a feasibility analysis of a context-aware communication platform that enables the delivery of data to mobile devices. Different types of information may be delivered, as produced by the execution of services which generate or retrieve them prior to transmission. Transmissions to the devices occur via wireless communication technologies, especially the Bluetooth. Called BlueYou, this platform makes use of context information and the profiles of mobile device to set policies for content delivery and content adaptation. Moreover, in order to expand the access to the services that generate the contents to deliver by BlueYou, the platform is integrated with a communication mechanism that creates an opportunistic ad hoc networking between mobile devices to transmit data to a particular recipient. As a result, it is expected that BlueYou can be widely used without requiring high deployment costs (financial, technological or time), and can serve as a basis for future studies involving communication patterns and interaction between users of mobile technologies.
Keywords: Computação móvel; Computação ubíqua; Sistemas de comunicação sem fio; Comunicação oportunística; Sistemas multimídia na internet; Mobile Computing; Ubiquitous computing; Wireless communication; Opportunistic communication; Multimedia services on the Internet; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO